The Jungle Book - Kipling, Rudyard, 1865-1936 (Worsop,Nottinghamshire Award Publications Limited, 2012)
Penned by English Nobel laureate Rudyard Kipling in 1894, The Jungle Book is a collection of allegorical stories that take place deep in the Indian jungle. The most famous stories of The Jungle Book are those featuring a young feral boy named Mowgli who was raised by wolves, is friends with a panther, and was educated by the animals of the jungle. Also popular in this collection is?Rikki-Tikki-Tavi," about a mongoose who protects his human family against cobras. A treasure trove of children's literature The Jungle Book from Word Cloud Classics is a chic and af.
Include Illustration
Keywords: Mowgli (Fictitious character) -- Jungle animals -- India